2012
DOI: 10.1021/ac300436m
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Binding-Guided Fluorescent Nanobiosensor for Acetylcholinesterase Inhibitors via Distance Modulation between the Fluorophore and Metallic Nanoparticle

Abstract: The magnitude of fluorescence enhancement was found to depend strongly on the distance between fluorophores and metal nanostructures in metal-enhanced fluorescence (MEF). However, the precise placement of the particle in front of the molecule with nanometer accuracy and distance control is a great challenge. We describe a method using acetylcholinesterase (AChE) to modulate the distance between a gold nanoparticle (AuNP) and the fluorophore 7-hydroxy-9H-(1,3-dichloro-9,9-dimethylacridin-2-one) (DDAO). We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…and DNA/CeO 2 complex, 360 nm lg(I562/I424) = −0.2713lgc – 2.312 (R2 = 0.995), RSD – 3.8% and 4.6% Thomas Schalkhammer [ 16 ] Fluorescein isothiocyanate NA NA Si-SiFs, 488 nm EF – 14 Samuel S.R. Dasary [ 39 ] Organophosphorus agents 1–25 μM 1 μM AuNPs, 395 nm Rsq 0.99, EF - 5 Fu Tang [ 19 ] PFV NA NA Ag@SiO 2 NPs, 405 nm EF – 1.3 Ying Wang [ 40 ] Adenosine 200 nM - 200 μM 48 nM AgNP aptasensor, 532 nm Rsq = 0.995, y = 0.395× + 0.3668 Yaodong Zhang [ 41 ] Paraoxon and Tacrine 0.5 μM–10 μM Paraoxon, 15 nM to 120 nM Tacrine 0.4 μM – Paraoxon, 10 nM - Tacrine AuNPs modified with DDAO-AChE, 447 nm EF - 6, RSD 1.7% Paraoxon, 2.1% Tacrine Yecang Tang [ 42 ] Glucose 2–52 mM 1,86 mM AgNP-CdSe QD, 400 nm EF – 9, Rsq = 0.991, RSD – 1.4% Eunji Gang [ 43 ] Glucose 1 μM – 1 mM 50 nM Ag@SiO2-entrapped hydrogel microarray, 580 nm EF – 4, Rsq = 0.997, RSD – 6.5% Tian Tian [ 24 ] Ascorbic acid 0.2–60 μM 25 nM Ag-CD nanohybrid, 500 nm Rsq = 0.986, Recoveries 92–106% Ramar Rajamanikandan [ 44 ] Dopamine 20–220 nM 0,35 nM GSH-Ag nanoclusters, 490 nm EF – 100, S/N – 3, Recoveries 96–98% Qiao Cheng [ 45 ] Heparin 0.025 to 2.5 μM 8.2 nM Ag-g-CNQDs, 450 nm ΔF = 133.4C + 25.18 (Rsq = 0.99) ...…”
Section: Small Organic Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…and DNA/CeO 2 complex, 360 nm lg(I562/I424) = −0.2713lgc – 2.312 (R2 = 0.995), RSD – 3.8% and 4.6% Thomas Schalkhammer [ 16 ] Fluorescein isothiocyanate NA NA Si-SiFs, 488 nm EF – 14 Samuel S.R. Dasary [ 39 ] Organophosphorus agents 1–25 μM 1 μM AuNPs, 395 nm Rsq 0.99, EF - 5 Fu Tang [ 19 ] PFV NA NA Ag@SiO 2 NPs, 405 nm EF – 1.3 Ying Wang [ 40 ] Adenosine 200 nM - 200 μM 48 nM AgNP aptasensor, 532 nm Rsq = 0.995, y = 0.395× + 0.3668 Yaodong Zhang [ 41 ] Paraoxon and Tacrine 0.5 μM–10 μM Paraoxon, 15 nM to 120 nM Tacrine 0.4 μM – Paraoxon, 10 nM - Tacrine AuNPs modified with DDAO-AChE, 447 nm EF - 6, RSD 1.7% Paraoxon, 2.1% Tacrine Yecang Tang [ 42 ] Glucose 2–52 mM 1,86 mM AgNP-CdSe QD, 400 nm EF – 9, Rsq = 0.991, RSD – 1.4% Eunji Gang [ 43 ] Glucose 1 μM – 1 mM 50 nM Ag@SiO2-entrapped hydrogel microarray, 580 nm EF – 4, Rsq = 0.997, RSD – 6.5% Tian Tian [ 24 ] Ascorbic acid 0.2–60 μM 25 nM Ag-CD nanohybrid, 500 nm Rsq = 0.986, Recoveries 92–106% Ramar Rajamanikandan [ 44 ] Dopamine 20–220 nM 0,35 nM GSH-Ag nanoclusters, 490 nm EF – 100, S/N – 3, Recoveries 96–98% Qiao Cheng [ 45 ] Heparin 0.025 to 2.5 μM 8.2 nM Ag-g-CNQDs, 450 nm ΔF = 133.4C + 25.18 (Rsq = 0.99) ...…”
Section: Small Organic Moleculesmentioning
confidence: 99%
“…In addition, this aptasensor showed high selectivity towards adenosine in the presence of other nucleosides. In the following year, the group of Dr. Zhang performed a series of experiments to test their newly designed AuNPs-based sensor for the detection of acetylcholinesterase (AChE) inhibitors [ 41 ]. This sensor is based on the combination of gold nanoparticles with a 7-hydroxy-9H-(1,3-dichloro-9,9-dimethylacridin-2-one) (DDAO) fluorophore bound to AChE.…”
Section: Small Organic Moleculesmentioning
confidence: 99%
“…One of factors affecting the enhancement magnitude is the distance between fluorophores and metal nanostructures. Interestingly, Zhang et al found that AChE could modulate the distance between AuNPs and fluorophore 7-hydroxy-9H-(1,3-dichloro-9,9-dimethylacridin-2-one) (DDAO) ( Figure 7 ) [ 63 ]. Binding of DDAO to AChE immobilized onto AuNPs lead to the enhancement of DDAO's fluorescence due to MEF ( Figure 7a ).…”
Section: Nanomaterials-based Optical Techniques For Detection Of Acetmentioning
confidence: 99%
“…( a ) Fabrication of AChE-AuNP conjugate via EDC/NHS coupling chemistry; ( b ) Metal enhanced fluorescence of DDAO bound with the active sites of AChE via distance regulation between the fluorophore and AuNP; ( c ) The fluorescence reduction via distance modulation due to AChE inhibitor binding. Reprinted with permission from [ 63 ]. Copyright 2012 American Chemical Society.…”
Section: Figurementioning
confidence: 99%
“…Glutamate is the major excitatory neurotransmitter in the central nervous system, [7][8][9][10][11] if the glutamate is in dysfunction, 12 it would lead to series diseases, such as epilepsy and schizophrenia, etc. Acetylcholinesterase (AChE) widely distributes in the central neural system and is bonded to the cellular membranes of excitable tissues, [13][14][15][16][17] and is a key enzyme playing a significant role in the nerve impulse transduction. Acetylthiocholine iodide (ATChI) is the substrate of acetylcholinesterase and nicotinic acetylcholine receptor agonist.…”
Section: Introductionmentioning
confidence: 99%